The Y172 Monoclonal Antibody Against p-c-Jun (Ser63) Is a Marker of the Postsynaptic Compartment of C-Type Cholinergic Afferent Synapses on Motoneurons - Gatius, Alaó; Tarabal, Olga; Cayuela, Paula; Casanovas, Anna; Piedrafita, Lídia; Salvany, Sara; Hernández, Sara; Soler, Rosa M.; Esquerda, Josep E.; Calderó, Jordi (Frontiers in Cellular Neuroscience, 2020)
C-bouton-type cholinergic afferents exert an important function in controlling motoneuron (MN) excitability. During immunocytochemical analysis of the role of c-Jun in MNs with a monoclonal (clone Y172) antibody against phospho (p)-c-Jun (serine [Ser]63), unexpected labeling was identified in the cell body cytoplasm. As predicted for c-Jun in adult spinal cord, very few, if any MNs exhibited nuclear immunoreactivity with the Y172 antibody; conversely, virtually all MNs displayed strong Y172 immunostaining in cytoplasmic structures scattered throughout the soma and proximal dendrites. The majority of these cytoplasmic Y172-positive profiles was closely associated with VAChT-positive C-boutons, but not with other types of nerve afferents contacting MNs. Ultrastructural analysis revealed that cytoplasmic Y172 immunostaining was selectively located at the subsurface cistern (SSC) of C-boutons and also in the inner areas of the endoplasmic reticulum. We also described changes in cytoplasmic Y172 immunoreactivity in injured and degenerating MNs. Moreover, we noticed that MNs from NRG1 type III-overexpressing transgenic mice, which show abnormally expanded SSCs, exhibited an increase in the density and size of peripherally located Y172-positive profiles. A similar immunocytochemical pattern to that of the Y172 antibody in MNs was found with a polyclonal antibody against p-c-Jun (Ser63) but not with another polyclonal antibody that recognizes c-Jun phosphorylated at a different site. No differential band patterns were found by western blotting with any of the antibodies against c-Jun or p-c-Jun used in our study. In cultured MNs, Y172-positive oval profiles were distributed in the cell body and proximal dendrites. The in vitro lentiviral-based knockdown of c-Jun resulted in a dramatic decrease in nuclear Y172 immunostaining in MNs without any reduction in the density of cytoplasmic Y172-positive profiles, suggesting that the synaptic antigen recognized by the antibody corresponds to a C-bouton-specific protein other than p-c-Jun. Our results lay the foundation for further studies aimed at identifying this protein and determining its role in this particular type of synapse.